Mindfulness in Counseling: Implementation of Counseling in the Society 5.0 - Hengki Yandri; Mudjiran Mudjiran; Yeni Karneli; Netrawati Netrawati (Indonesian Journal of Counseling and Development, 2023)
Counselors in the era of Society 5.0 are faced with new challenges in providing effective counseling services, such as the rapid adoption of technology, changes in how humans communicate and interact, and increasing levels of stress and emotional imbalance due to increased demands in life. Mindfulness can be an effective tool in helping counselors overcome these challenges and helping individuals strengthen their ability to cope with stress and emotional imbalances. Research methods used literature research. This research is conducted by researching and evaluating various reference materials and relevant literature to develop a coherent and logical synthesis that can be verified. The literature for this article is sourced from various platforms, including Publish or Perish, Google Scholar, open knowledge maps, and Scopus. Research results show that Mindfulness in counseling can be used to implement counseling in the era of Society 5.0